Newton's gravitation-force's classical average proof of a Verlinde's conjecture - Plastino, Ángel Luis (2018)
A surprising, gravity related Verlinde-conjecture, that generated immense interest, asserts that gravity is an emergent entropic force. We provided a classical proof of the assertion in [doi.org/j.physa.2018.03.019]. Here, we classically prove a related, second Verlinde-conjecture. This states that, at very large distances (r0), gravity departs from its classical nature and begins to decay linearly with r0.